The Effect of Perceived Waiting Time on Customer’s Satisfaction: A Focus on Fast Food Restaurant - Lahap, Johanudin; Iylia Azlan, Rabiatul; Anuar Bahri, Khairil; Mohd Said, Noraslinda; Abdullah, Dahlan; Adli Zain, Razlan (International Journal of Supply Chain Management, 2018)
Past research reveals that perceived waiting time was found to influence customer satisfaction and post-purchase behaviour. However, the present study aims to examine the effect of perceived waiting time on customer satisfaction in the context of fast food restaurant in Malaysia. In this study, simple random sampling method was employed and a total of 384 questionnaires were distributed. Consequently, 205 usable responses were successfully collected, representing 53% response rate. The data were analysed using SPSS software including descriptive analysis, reliability and validity test, factor analysis and correlation analysis. The result reveals that perceived waiting time significantly influence customer satisfaction towards fast food restaurants. Theoretically, this study confirmed the effects of perceived waiting time on customer satisfaction in the context of fast food restaurant. Practically, these findings are invaluable to fast food operators to improve the quality of their service delivery.Keywords: Perceived waiting time, Customer satisfaction, Fast food restaurant.